The Environmental Kuznets Curve - Evidence from Time Series Data for Germany - Hannes Egli (ETH Zurich, CER-ETH - Center of Economic Research, 2004)
In recent years, extensive literature on the Environmental Kuznets Curve lead- ing to optimistic policy conclusions has attracted great attention. However, the underlying cross-section estimations are not very reliable. Accordingly, this contribution uses time series data for a single country with dependable data quality : Germany. The results of the traditional reduced-form specification do not support the EKC hypothesis. However, with a specification in the tradi- tion of error correction models, which are more appropriate in the presence of non-stationary time series, it is found that the typical EKC pattern can be confirmed.
Keywords: Q00; Q20; 330; Environmental Kuznets Curve; Error Correction Model; Time Series Data; Umweltbelastung; Wirtschaftswachstum; Zeitreihenanalyse; Schätzung; Deutschland; Environmental Kuznets Curve; Kointegration